Interwencje humanitarne - Domagała, Arkadiusz (OTO Agencja Reklamowa, 2014)
The paper presents the position of international governmental organisations in regard to humanitarian intervention. After the end of the Cold War, the international community generally accept, under strict conditions, the possibility of the use of force when serious and massive violations of human rights take place. Nevertheless, a lot of organisations (e.g. ASEAN, OAS, LAS) remains reluctant to humanitarian intervention, considering it as an instrument of policy of the great powers. Other organizations (primarily the African Union) undergo a noticeable evolution in the perception of humanitarian intervention, in which the concept of the Responsibility to Protect plays a noteworthy role. The moderate supporters of human rights enforcement nowadays are mainly NATO and the European Union. However, also in the Charter of the African Union robust special measures for countries violating human rights are provided. Finally, the paper presents the determinants of the position of the organisations, it assess their readiness and political will to intervene, and attitude towards an intervention which is not authorized by the UN Security Council.
Keywords: organizacje międzynarodowe; politologia; prawa człowieka; demokracja; pomoc humanitarna; migracje; patologie; bezpieczeństwo; terroryzm międzynarodowy; ochrona środowiska